Low-grade myofibroblastic sarcoma: a case report of a child - Hamon Julien; Bourkis Amélie; Le Toux Guy (EDP Sciences, 2019)
Introduction: Myofibroblastic sarcomas are malignant tumors characterized by the increased proliferation of myofibroblasts; they are rare and have been recently discovered. Observation: A 14-year-old adolescent had a large lesion in the inside of her right mandible. The diagnosis, after a difficult histological analysis, was low-grade myofibrosarcoma. The patient was treated with non-interruptive hemimandibulectomy. Discussion: Low-grade myofibroblastic sarcoma is one of four types of myofibroblastic sarcomas recognized by the WHO in the 2001 classification. This classification allows us to determine a prognosis based on histological characteristics of the lesion. Conclusion: In all cases of low-grade myofibroblastic sarcoma, the preferred treatment is curative surgical resection; but still poses a problem in the prosthetic rehabilitation of oral lesion.